Efficacy of Mesotrione-Based Tank Mixtures and Application Timings Compared to Standards in Irrigated Corn - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2018)
Kochia, Russian thistle, and quinoa control was excellent regardless of treatment or rating date. Sunflower control at 10 DAPT was very good when Anthem Maxx (pyroxasulfone + fluthiacet) + Solstice (fluthiacet + mesotrione) + atrazine and glyphosate were applied EPOST, while green foxtail control was 94% with the same treatment at 68 DAPT. Palmer amaranth and green foxtail control at 68 DAPT was 93 and 91%, respectively, when SureStart II (acetochlor + flumetsulam + clopyralid) + atrazine and glyphosate were applied PRE followed by glyphosate POST. All herbicide-treated corn yielded 34 to 69 bu/a more grain than the untreated control. Yields among herbicide-treated corn were lowest when no EPOST or POST application was included.
Keywords: Single application; sequential applications